Genetic Diversity and Balancing Selection within the Human Phenylalanine Hydroxylase (PAH) Gene Region in Iranian Population - J Mowla (Iranian Journal of Public Health, 2012)
Background:Genetic diversity of three polymorphic markers in the phenylalanine hydroxylase(PAH) gene region including PvuII(a), PAHSTR and MspI were investigated.Methods:Unrelated individuals (n=139) from the Iranian populations were genotyped using primers specific to PAH gene markers including PvuII(a),MspI and PAHSTR. The amplified products for PvuII(a),MspI were digested using the appropriate restriction enzymes and separated on 1.5% agarose. The PAHSTR alleles were identified using polyacrylamide gel electrophoresis followed by silver staining. The exact size of the STR alleles was determined by sequencing. The allele frequency and population status of the alleles were estimated using PHASE, FBAT and GENEPOP software.Results: The estimated degree of heterozygosity for PAHSTR, MspI and PvuII (a) was 66%, 56% and 58%, respectively. The haplotype estimation analysis of the markers resulted in nine informative haplotypes with frequencies ≥5%.Moreover,the results obtained from Ewens-Watterson test for neutrality suggested that the markers were under balancing selection in the Iranian population.Conclusion:These findings suggested the presence of genetic diversity at these three markers in the PAH gene region. Therefore, the markers could be considered as functional markers for linkage analysis of the PAH gene mutations in the Iranian families with the PKU disease.